Desain Alat Filtrasi Effluent Instalasi Pengolahan Air Limbah menjadi Air Bersih - Amrullah, La Ode; Sumarlin, Sumarlin; Ilham, Ilham (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2021)
Recycling of liquid waste into clean water needs to be carried out by groups of large water users such as hospitals and industries by building recycling installations to maintain sustainable water use and efforts to minimize waste discharged into the environment. Effluent water in WWTPs, if managed further, can be used to fulfill clean water needs and reduce environmental pollution. This research makes a filtration device for filtering effluent WWTP water, laboratory tests show the content value of the pH parameter is 8.5 and the total coliform content value is 286 CFU/100 mL, when referring to the wastewater quality standards, the results are still in the waste water category. So that, it needs filtration treatment. Water quality after going through filtration treatment, the content value of the pH parameter is 6 and Total coliform 80 CFU/100 mL is still above the standard threshold referring to clean water quality standards.